A CHA-based DNA stochastic walker that traverses on cell membranes. Issue 3 (11th January 2021) - Hu, Yanlei; Chu, Xia
Abstract : Here, we introduce a catalytic hairpin assembly (CHA)-based DNA walker on cell membranes. Driven by DNA strand exchange, catalytic strands move on cell membranes and hairpin strands (H2) in the solution are loaded on cells. Abstract : DNA walkers, imitating protein motors, are a class of nucleic acid nanodevice that can move along a precisely defined "track". With a promising future in materials and biotechnology, DNA walkers have gained extensive attention among researchers. Here, we introduce a catalytic hairpin assembly (CHA)-based DNA walker on cell membranes. We designed hairpin strand (H1) modified cells as tracks. Driven by DNA strand exchange, catalytic strands move on cell membranes and other hairpin strands (H2) in the solution are loaded on cells. Additionally, we also introduce a CHA-based DNA motor and use the motor for cell membrane target sensing.